Value For Money-Based Financial Performance Measurement At The North Toraja Regency Government - Tikupasang, Medyoto; Haliah, Haliah; Kusumawati, Andi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
Financial performance is one of the most important issues in public sector organizations. Demanding transparency and accountability and supported by technological developments, several public sector organizations/institutions have published their performance reports, including their budget realization reports through their institutional websites. This study aims to determine the ability of the Regional Government of North Toraja Regency in 3 Fields of Government in regulating their budgets. Measurement will be done using Value For Money. This study used a descriptive qualitative approach. This research will measure the performance of the program on the activities carried out by collecting and presenting data on the 2021 North Toraja Regency Government APBD Realization Report in three areas of government, namely the Environment, the Culture and Tourism Office, and Transportation. The analysis will be carried out using the Value For Money method. Data collection is carried out by visiting the website of the Regional Government of North Toraja Regency and downloading the North Toraja Regency Regional Government APBD Realization Report from the site. The results of performance measurements in the activity program at the North Toraja Regency Government in the Field of Environmental Governance, the Culture and Tourism Office, and Transportation in 2021 which are measured using Value For Money can be said to be quite good in terms of economy and efficiency, but still need to improve performance in terms of effectiveness.